The Scale of Evaluating Instruction in Pandemic Process: Development, Validation, and Reliability - Tutal, Özgür; Kayalı, Bünyami; Yavuz, Mehmet; Hasançebi, Mehmet; Yeşildağ-Hasançebi, Funda (Pedagogika, 2023)
The study aims to develop a scale for determining student views on distance instruction, hybrid instruction, and back-to-school process after the pandemic. The study data were obtained from 442 students. EFA and CFA were performed to determine the scale‘s construct validity. Moreover, to decide the data collection tool‘s reliability, item analysis was conducted and internal consistency coefficients were estimated. Based on the results obtained from the validity and reliability analysis of the scale, it can be said that the Scale of Evaluating Instruction in Pandemic Process (SEIPP) is valid and reliable.